A framework for stakeholder engagement in the adoption of new anti-malarial treatments in Africa: a case study of Nigeria - Mokuolu, O.A.; Bolarinwa, O.A.; Tindana, P.; et al. (Malaria Journal, 2023)
Background Recent reports of artemisinin partial resistance from Rwanda and Uganda are worrisome and suggest a future policy change to adopt new anti-malarials. This is a case study on the evolution, adoption, and implementation of new anti-malarial treatment policies in Nigeria. The main objective is to provide perspectives to enhance the future uptake of new anti-malarials, with an emphasis on stakeholder engagement strategies. Methods This case study is based on an analysis of policy documents and stakeholders’ perspectives drawn from an empirical study conducted in Nigeria, 2019–2020. A mixed methods approach was adopted, including historical accounts, review of programme and policy documents, and 33 qualitative in-depth interviews and 6 focus group discussions. Results Based on policy documents reviewed, the adoption of artemisinin-based combination therapy (ACT) in Nigeria was swift due to political will, funding and support from global developmental partners. However, the implementation of ACT was met with resistance from suppliers, distributors, prescribers, and end-users, attributed to market dynamics, costs and inadequate stakeholder engagement. Deployment of ACT in Nigeria witnessed increased developmental partner support, robust data generation, ACT case-management strengthening and evidence on antimalarial use in severe malaria and antenatal care management. A framework for effective stakeholder engagement for the future adoption of new anti-malarial treatment strategies was proposed. The framework covers the pathway from generating evidence on drug efficacy, safety and uptake; to making treatment accessible and affordable to end-users. It addresses which stakeholders to engage with and the content of engagement strategies with key stakeholders at different levels of the transition process. Conclusion Early and staged engagement of stakeholders from global bodies to community level end-users is critical to the successful adoption and uptake of new anti-malarial treatment policies. A framework for these engagements was proposed as a contribution to enhancing the uptake of future anti-malarial strategies
Research Article
Keywords: Artemisinin resistance; Stakeholder engagement; Artemisinin-based combination therapY